2013
DOI: 10.1007/s10071-013-0605-3
|View full text |Cite
|
Sign up to set email alerts
|

Switching strategies: a dolphin’s use of passive and active acoustics to imitate motor actions

Abstract: Scientists have long debated the extent to which animals can imitate. Observations of bottlenose dolphins suggest a sophisticated capacity for social imitation, but little is known about the nature of these abilities. Here, we explore the behavioral mechanisms underlying a dolphin's ability to copy motor actions while blindfolded (i.e., wearing eyecups). When a dolphin was asked to imitate a dolphin, a human, and then another dolphin blindfolded, his accuracy remained relatively consistent across models. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Unfortunately, systematic comparisons between studies are difficult because studies vary in terms of the criterion of correct performance, the number and type of actions performed by the demonstrator (e.g., vocal versus motor; transitive versus intransitive), and the kind of demonstrator are also variable (e.g., conspecific, human, computer). For example, compared to dolphins Yulka´s level of correct performance remained high after making the first correct matching ( Table 2 ) as in Jaakkola et al’s [ 49 ] study of motor imitation the researchers found that in the sighted condition (similar to our study) the dolphin’s matching accuracy of 19 motor behaviors was 61%. On the other hand, compared to killer whales, Yulkas’s generalization of the copy command was slower as in the Abramson et al’s [ 35 ] study, familiar behaviors performed by the demonstrator were copied before the 8 th trial and many of them on the first attempt (range = 57–93%).…”
Section: Discussionsupporting
confidence: 84%
“…Unfortunately, systematic comparisons between studies are difficult because studies vary in terms of the criterion of correct performance, the number and type of actions performed by the demonstrator (e.g., vocal versus motor; transitive versus intransitive), and the kind of demonstrator are also variable (e.g., conspecific, human, computer). For example, compared to dolphins Yulka´s level of correct performance remained high after making the first correct matching ( Table 2 ) as in Jaakkola et al’s [ 49 ] study of motor imitation the researchers found that in the sighted condition (similar to our study) the dolphin’s matching accuracy of 19 motor behaviors was 61%. On the other hand, compared to killer whales, Yulkas’s generalization of the copy command was slower as in the Abramson et al’s [ 35 ] study, familiar behaviors performed by the demonstrator were copied before the 8 th trial and many of them on the first attempt (range = 57–93%).…”
Section: Discussionsupporting
confidence: 84%
“…They also were more likely than Kimbit to use multiple strategies within a trial. Dolphins can switch strategies when task parameters change (Jaakkola, Guarino, Rodriguez, & Hecksher, 2013;Kuczaj, Gory, & Xitco, 2009), and we suspect that the dolphins in this study varied their strategies to keep the task interesting, much as dolphins modify their play to keep it interesting (Kuczaj et al, 2006;Kuczaj & Walker, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Nonetheless, in this particular case, the plausibility arguments are unusually strong, for a number of reasons. First, the motor imitation capabilities of bottlenose dolphins are well established [17,18], so social learning has to be a candidate for explaining the spread of tail walking. Second is the arbitrary nature of the behaviour-it is a highly energetic display, so likely costly, that produces nothing energetically to offset that cost.…”
Section: Discussionmentioning
confidence: 99%